2019
DOI: 10.1111/adb.12797
|View full text |Cite
|
Sign up to set email alerts
|

Accumbens neuroimmune signaling and dysregulation of astrocytic glutamate transport underlie conditioned nicotine‐seeking behavior

Abstract: Nicotine self‐administration is associated with decreased expression of the glial glutamate transporter (GLT‐1) and the cystine‐glutamate exchange protein xCT within the nucleus accumbens core (NAcore). N‐acetylcysteine (NAC) has been shown to restore these proteins in a rodent model of drug addiction and relapse. However, the specific molecular mechanisms driving its inhibitory effects on cue‐induced nicotine reinstatement are unknown. Here, we confirm that extinction of nicotine‐seeking behavior is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 81 publications
2
28
1
Order By: Relevance
“…In mice, microglial morphology changes in striatal tissues have been reported following chronic treatment with nicotine and undergoing withdrawn, which were associated with the release of pro-inflammatory cytokines and increase in ROS ( Adeluyi et al, 2019 ; Saravia et al, 2019 ). Increased TNFα levels have been reported in the nucleus accumbens of rats during cue-induced nicotine seeking ( Namba et al, 2020 ), and an increased TNFα gene expression has also been described in the prefrontal cortex of nicotine- and cigarette smoke-exposed rats ( Lau et al, 2012 ). It is well established that through the activation and nuclear translocation of the transcription factor NF-κB, TNFα induces the synthesis of various pro-inflammatory cytokines, including IL-6 ( Shimizu et al, 1990 ; Kunsch and Rosen, 1993 ; Ping et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, microglial morphology changes in striatal tissues have been reported following chronic treatment with nicotine and undergoing withdrawn, which were associated with the release of pro-inflammatory cytokines and increase in ROS ( Adeluyi et al, 2019 ; Saravia et al, 2019 ). Increased TNFα levels have been reported in the nucleus accumbens of rats during cue-induced nicotine seeking ( Namba et al, 2020 ), and an increased TNFα gene expression has also been described in the prefrontal cortex of nicotine- and cigarette smoke-exposed rats ( Lau et al, 2012 ). It is well established that through the activation and nuclear translocation of the transcription factor NF-κB, TNFα induces the synthesis of various pro-inflammatory cytokines, including IL-6 ( Shimizu et al, 1990 ; Kunsch and Rosen, 1993 ; Ping et al, 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest a likely role of astrocytes and microglia in nicotine addiction. Cue-induced reinstatement of nicotine self-administration and chronic nicotine exposure in rats is associated with increased tumor necrosis factor-alpha (TNFα) levels in the prefrontal cortex and nucleus accumbens ( Royal et al, 2018 ; Namba et al, 2020 ). Consistent with the above, studies in the authors’ laboratory showed that both chronic nicotine intake and nicotine-conditioned place preference were associated with changes in markers of glial inflammation, including an increased length and thickness of astrocytic processes and increased microglial density (cell number/area) in the rat hippocampus ( Quintanilla et al, 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and xylazine (8 mg/kg, i.m.) and underwent surgical implantation of intravenous jugular catheters as well as stereotaxically implanted guide cannulae targeting the NAcore as previously described ( Leyrer-Jackson et al, 2020 ; Namba et al, 2020 ). Intravenous jugular catheters (made from polyurethane tubing; BTPU-040; Instech) were inserted 2.5–3 cm into the right jugular vein and were threaded subcutaneously to the posterior side of the animal where it was connected to an indwelling back port (Instech).…”
Section: Methodsmentioning
confidence: 99%
“…and xylazine (8 mg/kg, i.m.) and underwent surgical implantation of intravenous jugular catheters as well as stereotaxically implanted guide cannulae targeting the NAcore as previously described [30,31].…”
Section: Surgical Proceduresmentioning
confidence: 99%